Admission dental examination: protocol and its importance in the diagnosis of oral pathology - Mário Marques Fernandes; Mara Rosângeles de Oliveira; Rafael Bender Carpena de Menezes de Oliveira; Talita Lima de Castro; Luiz Renato Paranhos; Eduado Daruge Júnior (Universidade Estadual de Campinas, 2015)
The aim of this paper is to describe an efficient clinical protocol used in admittance dental examinations, highlighting the importance of this evaluation in the diagnosis of oral pathologies. Two admission case reports in which gingival abscess and radiopaque apical lesion were found during the examination are presented for illustration purposes. A clinical examination in the admission inspection is the main factor for a good selection of treatment and prevention of future difficulties. The admission dental examination by means of a standardized clinical approach including clinical interview, physical examination and complementary exams, avoids the person to be admitted to the public service while having some pathology that might compromises his/her capacity of handling the selected function, preventing absenteeism for dental reasons and consequently a cost to the state and functional repercussion to the server.